Magazines and the American experience : highlights from the collection of Steven Lomazow, MD - Lomazow, Steven (The Grolier Club, 2020)
Preface : Magazines! -- "Magazine magic" -- Introduction : The early history of the magazine industry -- A chronology of American magazines. Building a nation : 1733-92 -- A house divided : 1793-1850 -- The industrial age : 1851-92 -- America and the world : 1893-1945 -- The information age 1946-present -- Specialty magazines. The urge to reform : radical magazines -- A nation of readers : literary magazines -- American avant-gardism : little magazines -- Literature for the people : pulp magazines -- "What fools these mortals be!" : humor magazines -- Great American pastimes : sports magazines -- Separate and unequal : African American magazines -- The show must go on : theater, movie, radio, and television magazines -- On the move : transportation magazines -- Images of a nation : art and magazines.